Local content policies in resource-rich countries - Kalyuzhnova, Yelena; Nygaard, Andi; Omarov, E. S.; Saparbayev, Abdizhapar (Euro-Asian studies., 2016)
This book analyses the role of local content (LC) policy in the economic development of five resource-rich countries: Brazil, Kazakhstan, Norway, Russia and the UK. The authors situate LC policy within a framework of sustainability in the form of industrial diversification and innovation-led growth, and examine how effective LC policies are in facilitating sectoral and economy-wide catching up. Structured in five chapters, the book begins with an introduction and then presents an overview of LC definitions and situates LC policies within a framework of economic development. The third chapter compares specific examples of LC development and highlights variations in practice as well as learning across case countries. The fourth chapter focuses on macro-economic, micro-economic and institutional challenges conditioning LC development and the ability of LC policies to assist innovation-led growth. The authors conclude by examining what the future holds for LC policies and their role in promoting economic growth and addressing the wider social, political and economic challenges in resource-rich countries.